La figura de la Malinche en la literatura hispana del siglo XX: La aprendiz de bruja de Alejo Carpentier, Todos los gatos son pardos de Carlos Fuentes y Jubileo en el Zócalo de Ramón Sender - Csikós, Zsuzsanna (Acta Hispanica, 2013)
The article analyses the figure of La Malinche in three least-known theatrical texts of the 20th century Hispanic Literature: La aprendiz de bruja of the cuban writer, Alejo Carpentier, Todos los gatos son pardos of the mexican Carlos Fuentes and the spanish Ramón Sender’s Jubileo en el Zócalo. Starting from the historical events and the reality will be examined her enigmatic rol, her tragic and contradictory destination in these fictions. The different views of the three works make it possible to present the indian woman’s and her nation’s identity.